PENGARUH TERAPI MUSIK KLASIK TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU BERSALIN KALA I At BPM Siti Mudrikatin, SST., M. Kes TAHUN 2019: PENGARUH TERAPI MUSIK KLASIK TERHADAP PENURUNAN INTENSITAS NYERI PADA IBU BERSALIN KALA I At BPM Siti Mudrikatin, SST., M. Kes TAHUN 2019 - Rista Dian Anggraini (STIKes Buleleng, 2020)
Classical Music Therapy is effective because it is shown to show the effects of reducing anxiety and depression, and relieving pain. Objective: To determine the effect of classical music therapy on decreasing the intensity of pain in the first mother's uterus at BPM Siti Mudrikatin, SST., M.Kes in 2019. Research Methods: quasy experiment using 2 groups: the experimental group and the control group. . Both groups pretested to observe pain intensity. The experimental group was given classical music therapy while the control group was not given classical music therapy. Sampling using consecutive sampling, sample size of 36 people, 18 control groups and 18 intervention groups. Results: The results of the bivariate analysis using the 2 unpaired group test found that the intervention group on average was lower than the average of the control group. This difference was found to be statistically significant with p <0.05 with a value <0.0001, so it can be concluded that there are differences in pain felt between maternity mothers who were given classical music and those who were not given.